2018
DOI: 10.1111/tpj.13897
|View full text |Cite
|
Sign up to set email alerts
|

Hunting the main player enabling Chlamydomonas reinhardtii growth under fluctuating light

Abstract: SUMMARYPhotosynthetic organisms have evolved numerous photoprotective mechanisms and alternative electron sinks/pathways to fine-tune the photosynthetic apparatus under dynamic environmental conditions, such as varying carbon supply or fluctuations in light intensity. In cyanobacteria flavodiiron proteins (FDPs) protect the photosynthetic apparatus from photodamage under fluctuating light (FL). In Arabidopsis thaliana, which does not possess FDPs, the PGR5-related pathway enables FL photoprotection. The direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 65 publications
6
90
1
Order By: Relevance
“…Further analysis of candidate mitochondrial ETC components revealed an accumulation of selective mitochondrial proteins important for ATP production such as COXIIb and ATP synthase (mitochondrial/chloroplast), along with concomitant reduction in AOX1 levels following TOR kinase inhibition ( Figure 3C). Such compensatory mechanisms leading to an increase in COX have been previously reported in chloroplast mutants defective in cyclic electron transport mediated by PGR5/PGRL1 (Jokel, Johnson, Peltier, Aro, & Allahverdiyeva, 2018). Interestingly, loss-offunction mutant pgr5/pgrl1 also exhibited a reduction in PsaA levels of PSI, which we were able to corroborate in TOR kinase inhibited cells (Figure 2c) that also showed enhanced mitochondrial COX protein levels ( Figure 3C).…”
Section: This Results Is Consistent With a Recent Phospho-proteomic Stsupporting
confidence: 88%
“…Further analysis of candidate mitochondrial ETC components revealed an accumulation of selective mitochondrial proteins important for ATP production such as COXIIb and ATP synthase (mitochondrial/chloroplast), along with concomitant reduction in AOX1 levels following TOR kinase inhibition ( Figure 3C). Such compensatory mechanisms leading to an increase in COX have been previously reported in chloroplast mutants defective in cyclic electron transport mediated by PGR5/PGRL1 (Jokel, Johnson, Peltier, Aro, & Allahverdiyeva, 2018). Interestingly, loss-offunction mutant pgr5/pgrl1 also exhibited a reduction in PsaA levels of PSI, which we were able to corroborate in TOR kinase inhibited cells (Figure 2c) that also showed enhanced mitochondrial COX protein levels ( Figure 3C).…”
Section: This Results Is Consistent With a Recent Phospho-proteomic Stsupporting
confidence: 88%
“…Exploration of mechanistic diversity in different photosynthetic organisms is critical to better understand their evolution and the physiological role of these reactions. The PGR5/PGRL1-mediated CEF has been identified in plants (Munekage et al, 2002;DalCorso et al, 2008), and corresponding genes were also found in green eukaryotic algae (Peltier et al, 2010;Jokel et al, 2018). The chloroplast multimeric NDH complex (NDH-1) (Shikanai et al, 1998) acts as a ferredoxin-dependent PQ reductase with proton-pumping activity and it has been characterized in angiosperms, but its presence was described also in the Streptophyta alga Klebsormidium flaccidum (Hori et al, 2014).…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, NO photoreduction could play a regulatory role during anaerobic photosynthesis, as shown for other minor pathways such as chlororespiration under aerobic conditions (30,36). In photosynthetic organisms, FLVs have so far been solely involved in oxygen reduction, this electron valve being critical for growth under fluctuating light conditions (22,26,37,38). We show here that FLVs play a dual function in the reduction of O2 as well as NO in chlorophytes, and that the significance of this duality on the functioning and regulation of photosynthesis should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the contribution of FLVs to NO photoreduction, we analyzed NO and N2O exchange during dark to light transients in three previously characterized flvB mutants (22). These mutants are impaired in the accumulation of both FLVB and FLVA subunits (22,25,26). In the dark, no significant difference in NO reduction neither in N2O production were found between the three flvB mutant as compared to the control (Fig.…”
Section: Light-dependent N2o Photoproduction Mostly Relies On Flvsmentioning
confidence: 99%